Etichal Issues in Primary Health Care from Centro de Salud Familiar de Paine - Contreras Aravena, Luis (Acta Bioethica, 2017)
This paper attempts to identify which clinical ethical problems experienced in primary care health, particularly in CESFAM Paine, Chile, also differentiate according profession and life cycle of the patient. It’s a qualitative and descriptive study based on semi-structured interviews with experts in bioethics and CESFAM’s workers, both professional and technical. We conclude that conflicts exist, and are determined by the clash of values in each decision making, and the lack of virtuosity of the workers. The professionals have similar problems, which is given by the interdisciplinary work done in the APS, in addition to be individual depending on the stage of the life cycle of the patient. It’s necesary to perform deeper studies on these issues.